Bifidobacterium longum subsp. infantis ATCC 15697 α-Fucosidases Are Active on Fucosylated Human Milk Oligosaccharides - Sela, David A. (American Society for Microbiology, 2012)
Bifidobacterium longum subsp. infantis ATCC 15697 utilizes several small-mass neutral human milk oligosaccharides (HMOs), several of which are fucosylated. Whereas previous studies focused on endpoint consumption, a temporal glycan consumption profile revealed a time-dependent effect. Specifically, among preferred HMOs, tetraose was favored early in fermentation, with other oligosaccharides consumed slightly later. In order to utilize fucosylated oligosaccharides, ATCC 15697 possesses several fucosidases, implicating GH29 and GH95 α-l-fucosidases in a gene cluster dedicated to HMO metabolism. Evaluation of the biochemical kinetics demonstrated that ATCC 15697 expresses three fucosidases with a high turnover rate. Moreover, several ATCC 15697 fucosidases are active on the linkages inherent to the HMO molecule. Finally, the HMO cluster GH29 α-l-fucosidase possesses a crystal structure that is similar to previously characterized fucosidases.